Testing the excitability of human motoneurons - Mcneil, Chris J.; Butler, Jane E.; Taylor, Janet L.; Gandevia, Simon C. (Frontiers in Human Neuroscience, 2013)
The responsiveness of the human central nervous system can change profoundly with exercise, injury, disuse or disease. Changes occur at both cortical and spinal levels but in most cases excitability of the motoneurone pool must be assessed to localize accurately the site of adaptation. Hence, it is critical to understand, and employ correctly, the methods to test motoneurone excitability in humans. Several techniques exist and each has its advantages and disadvantages. This review examines the most common techniques that use evoked compound muscle action potentials to test the excitability of the motoneurone pool and describes the merits and limitations of each. The techniques discussed are the H-reflex, F-wave, tendon jerk, V-wave, cervicomedullary motor evoked potential, and motor evoked potential. A number of limitations with these techniques are presented.